Assessment of Plasma Deposition Parameters for DED Additive Manufacturing of AA2319 - Paula Rodríguez-González; Erich Neubauer; Enrique Ariza; Leandro Bolzoni; Elena Gordo; Elisa María Ruiz-Navas (Journal of Manufacturing and Materials Processing, 2023)
Arc-directed energy deposition using wire as feedstock is establishing itself as a 3D printing method capable of obtaining additively manufactured large structures. Contrasting results are reported in the literature about the effect of the deposition parameters on the quality of the deposited tracks, as it is highly dependent on the relationship and intercorrelations between the individual input parameters, which are generally deposition-technique-dependent. This study comprehensively analysed the effect of several deposition parameters and clarified their interactions in plasma metal deposition of Al alloys. It was found that, although no straightforward correlation between the individual input parameters investigated and the measured output deposition track’s quality aspects existed, the input current had the greatest effect, followed by the wire feed speed and its interaction with the input current. Moreover, the greatest effect of changing the shielding gas atmosphere, including the gas mixture, flow rate and plasma flow, was on the penetration depth, and fine-tuning the frequency/balance ratio and the preheating of the deposition substrates reduced the amount of porosity. This study demonstrates that well-deposited multi-layer walls made out of Al alloys can successfully be achieved via plasma metal deposition.